Analysis of factors influencing the number of outpatient facilities for elderly patients - MATSUDA, Shinya (Review of Japan Society of Health Support Science, 2023)
【Objective】 In Japan, the issue of elderly people visiting multiple facilities is a topic of debate. This issue is also important when considering the role of family doctors. In this paper, we use medical and nursing care data from a municipality in western Japan to analyze the current situation and related factors and discuss the role of family doctors.【Materials and methods】 The data was generated using medical receipts （National Health Insurance and Medical Care Insurance for the Elderly） and long term care insurance receipts from one local government （prefectural level） in western Japan. Using this database, the number of medical institutions and dispensing pharmacies where subjects aged 65 and over visited as outpatients, the number of days of outpatient visits, and the types and number of illnesses diagnosed, as well as the total number of months nursing care insurance services were used were calculated.【Results】 The main results of the multivariate analysis on the number of outpatient visits are as follows （numbers are multiple regression coefficients）.・There was a statistically significant difference in outpatient visits and the number of days of outpatient visits, with both being higher in urban medical areas A and B and lower in medical area G, which is a mountainous region.・Concerning the impact of illness or injury on the number of outpatient visits, the number of institutions visited was higher for those with eye disease （1.06）, ear disease （0.68）, skin disease （0.57）, spinal disorders （0.42）, malignant tumors （0.64）, and cerebrovascular disease （CVD） （0.44）.・Concerning the impact of illness or injury on the number of days of outpatient visits, the number of days of outpatient visits was higher for those with schizophrenia （9.6）, mood disorder （4.1）, eye disease （6.7）, ear disease （5.4）, skin disease （6.4）, lower limb joint disorders （9.6）, spinal disorders （9.5）, osteoporosis （5.0）, renal failure （4.0）, and dementia （4.9）.・Those who use long term care insurance have a lower use of medical institutions （－0.48）.【Discussion】 In urban areas with abundant medical resources, it is natural for elderly patients who have a chronic internal medicine disease and a family doctor specializing in internal medicine to go to clinics that specialize in dermatology, ophthalmology, otolaryngology, orthopedics, or other specialties for their injuries or illnesses. Therefore, if there are attempts to restrict such visits, it is clear that patients will be dissatisfied. In light of this situation, the immediate challenge in urban areas is to create a system of family doctors that functions as a network. On the other hand, in mountainous areas with scarce medical resources, the reality is that “internal medicine clinics and other facilities already function as family doctors in a general practitioner role.” Therefore, in such areas, the strengthening of the general practitioner function should be incorporated into the framework of lifelong training for doctors.